Local institutional development and relief in Ethiopia: A Kire-based seed distribution programme in north Wollo - Pratten, D (Wiley, 1997)
Highlighted here is the important role played by community‐based organisations in relief supply operations. In the context of an emergency seed supply project in northern Ethiopia in 1995, it examines the participation of burial societies, known as kires, in targeting, distribution and management. The paper illustrates that factors of local institutional legitimacy, transparency and accountability are central, both to the effective representation of community views and to long‐term partnerships between local institutions and non‐governmental organisations.